Cellulose Nanowhisker (CNW)/Graphene Nanoplatelet (GN) Composite Films With Simultaneously Enhanced Thermal, Electrical and Mechanical Properties - Liu, Dongyan; Dong, Yu; Liu, Yueyue; Ma, Na; Sui, Guoxin (Frontiers in Materials, 2019)
Transparent cellulose nanowhisker (CNW)/graphene nanoplatelet (GN) composite films were produced via sonication mixing and solution casting methods. Such composite films exhibited improved thermal, electrical and mechanical properties. The material morphologies and microstructures were examined using scanning electronic microscopy (SEM), X-ray diffraction (XRD) analysis and Raman spectroscopy. Strong interaction was detected when CNWs were randomly attached onto graphene sheets, as evidenced by SEM images obtained in this study. In particular, the addition of GNs into CNWs had significant effect on the thermal behavior of composite films. The melting temperature (Tm) and initial thermal decomposition temperature (Tid) of CNW films were both increased by 23.2, 29.3, 26.3°C, and 70.2, 88.4, 87.8°C with the inclusions of 0.1, 0.25, and 0.5 wt% GNs, respectively. The electrical conductivity of composite films was enhanced in a monotonically increasing manner with the maximum level of 4.0 × 10−5 S/m detected at the GN content of 0.5 wt%. Their tensile strength was also improved by maximum 33.7% when increasing the GN content up to 0.25 wt% as opposed to that of CNW films. Such CNW/GN composite films can be potentially used in green anti-static and electronic packaging applications.